Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Targeting viral Fe-S clusters with TEMPOL confers broad-spectrum anti-coronavirus activity - Leyu Hu; Lexi Gao; Xingwei Fu; Zesheng Rong; Yue Cheng; Yuhan Hou; Lu Han; Xin Ran; Guiwen Guan; Ting Zhou; Lingling Chang; Xiaomin Zhao; et al. (Veterinary Microbiology, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

GF7S: A large-scale GaoFen-7 stereo dataset and self-supervised adaptation of FoundationStereo for high-resolution DSM generation - Yinxia Cao; Fenzhen Su; Dongjie Fu; Wenzhou Wu; Fengqin Yan; Rong Fan; Hao Chen; Xin Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Integrated network toxicology, transcriptomics, and metabolomics revealed the potential mechanisms of aluminum-induced testicular injury - Siyu Liao; Liqing Huang; Yusi Zhou; Xin Zhang; Shaofeng Huang; Linjun Yu; Shiman Zhu; Wei Chen; Rong Wang; Haimei Qin (Food and Chemical Toxicology, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Characterization of CYP402C5 associated with field resistance to three neonicotinoids in Bemisia tabaci - Chao Wang; Rong Zhang; Jing Yang; Mingjiao Huang; Hantang Lu; Ying Zhang; Youjun Zhang; Junkai Li; Xin Yang (Pesticide Biochemistry and Physiology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

The modulating role of ENSO on the spatial variability of Asian summer monsoon precipitation over the past 2000 years at multidecadal timescales - Zhicong Huang; Xin Mao; Jingxuan Yang; Rong Qin; Xingqi Liu (Global and Planetary Change, 2026)

Impacts of trunk height, tree planting density, and wall heating on flow and pollutant dispersion inside an urban street canyon - Yuan-Dong Huang; Yan-Jiao Jiang; Rong Ji; Ke-Xin Wang; Meng-Xin Chai; Yang Luo; Peng-Yi Cui (Environmental Fluid Mechanics, 2026)

Rapid recovery of trilobites after the Late Ordovician mass extinction (LOME) - Xin Wei; Renbin Zhan; Jiayu Rong; Bing Huang; Guanzhou Yan (Earth-Science Reviews, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Is ecological quality of river-connected lake basin higher than disconnected lake basins in the lower reaches of the Yangtze River, China? - Dong-zheng Yu; Ying Huang; Jing-wei Yang; Xiang-rong Song; Xin-sheng Chen (Environmental Monitoring and Assessment, 2026)

Apportioning nitrate sources via dual isotope, PMF and SIAR in a complex urban river network during flood season: Implications for engineered mitigation strategies - Xin Wang; Qiaoyun Lin; Zhixiong Huang; Yihua Cai; Wenjing Wang; Nan Rong; Siye Wei; Renren Wu; Quan Zhou (Journal of Water Process Engineering, 2026)

The transcription factor SlPLATZ22 negatively regulates salinity tolerance in tomato plants - Xin Li; Fei Ding; Niannian Zhou; Zheng Chen; Jiahui Huang; Fangling Jiang; Carl-Otto Ottosen; Ron Mittler; Rong Zhou; Zhen Wu (Journal of Plant Physiology, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

A scalable human liver-on-a-chip platform for predictive safety assessment - Gauri Kulkarni; Lizao Chen; Jing Sang; Ji Hye Seo; Romain Grall; Yunfang Wang; Paige Gilbride; Yu-Chieh Yuan; Matthew Albaum-Getzen; Jenna McCormack; Jingzhe Ma; Alyssa Fanelli; et al. (Toxicology, 2026)

The role of heterogeneity in groundwater chemistry and mixing within the critical zone of a volcanic rock hillslope - Tao Yang; Jiu Jimmy Jiao; Rong Mao; Xin Luo; Jeffrey Wong; Jinchao Zuo; Wenli Hu; Jiawei Liang; Yanqiong Huang; Xiaoyan Shi (Journal of Hydrology, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Integrated Analysis of Midgut Transcriptome and Microbiome Reveals That Manganese‐Induced Dysbiosis Drives Metabolic Disruption and Developmental Toxicity in Bombyx mori - Lei Xin; Yazhen Chen; Delong Guan; Lida Huang; Yiwei Lv; Wantao Rong; Xiaodong Li (Environmental Microbiology, 2026)
Manganese (Mn) contamination poses a significant environmental threat, yet the mechanisms underlying its toxicity remain poorly characterised. Here, we used an integrative multi‐omics approach to elucidate how dietary Mn disrupts the gut‐microbiome axis in the silkworm, Bombyx mori . High‐dose Mn exposure triggered severe, dose‐dependent growth retardation, reducing larval weight by 55.1%. This was concurrent with profound gut microbiome dysbiosis, evidenced by reduced bacterial diversity, community homogenisation and a sharp decline in beneficial genera such as Delftia , alongside the complete elimination of key commensals like Bifidobacterium . Host midgut transcriptomics revealed 1255 differentially expressed genes, with significant upregulation of detoxification and stress pathways and marked suppression of genes involved in nutrient metabolism. Critically, integrative analysis demonstrated a strong correlation between microbiome disruption and host metabolic gene expression, suggesting that Mn toxicity operates by disrupting the gut microbiome‐host metabolic axis. Our findings provide crucial mechanistic insights into heavy metal ecotoxicology and highlight the vulnerability of beneficial insect‐microbe symbioses to environmental contamination, with important implications for sustainable agriculture in metal‐polluted regions.

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Microglial Necroptosis Mediated by RIPK3 Leads to Retinal Ganglion Cell Apoptosis Through the Release of FGF2 After Ischemia/Reperfusion - Jian Liu; Anping Ma; Guangyi Huang; Wen Hu; Xin Xu; Rong Huang; Yaguang Hu; Qiaochu Cheng; Yanlin Feng; Dan Ye; Fan Xu; Aimin Sang (Journal of Molecular Neuroscience, 2025)

Chronic dietary exposure to BDE-47 can induce inflammatory responses in the brain of common carp (Cyprinus carpio) and further trigger neurotoxicity through the 5-HT pathway - Huimin Sun; Youlian Liu; Yujie Huang; Mengbin Yuan; Zujun Ye; Rong Yang; Fuqiang Sha; Ni Tang; Bo Zhou; Defang Chen; Zhiqiong Li; Xin Zhang (Science of The Total Environment, 2025)

Synergistic effects of pre-harvest drought and shade on flavor and aroma enhancement in fermented tea: Insights into JA/ABA signaling and metabolic regulation - Chenyu Shao; Xinyu Peng; You Li; Ziqi Chen; Xin Li; Rong Xu; Shuqi Qiu; Yuqi Luo; Jie Liu; Jianan Huang; Zhonghua Liu; Li Niu; et al. (Food Chemistry, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Editorial for Special Issue: Sino-German P&RS Cooperation: Applications, Methods, Reviews - Xin Wang; Ludwig Hoegner; Rong Huang; Lei Ma; Yusheng Xu (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)

Room temperature natural light promoted DMSO/O2-catalyzed N-acylation reaction of imidazoles/triazoles with cyclopropenones - Guo-Dong Shen; Zhi-Rong Zhao; Kun Bi; Yi Man; Jun-Tong Liu; Xian-Qiang Huang; Xin Lv (Molecular Diversity, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Biofilm community structure and loading effect of netted cages for offshore aquaculture in the Western Yellow Sea - Ming-Shan Sun; Chun-Wei Bi; Liu-Yi Huang; Rong-Ping Liu; Xin-Xing You; Shu-Yue He (Biosystems Engineering, 2025)

Why is the combined treatment of copper and aluminum more toxic to citrus than single factor treatment? - Wen-Shu Chen; Ti Wu; Tian-Tian Xia; Liang-Yuan Tong; Fei Lu; Xin Ye; Jiuxin Guo; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2025)

Enhanced microbial degradation of methylmercury by montmorillonite - Qin Liu; Hui Yin; Baohua Gu; Xin-Quan Zhou; Xiaolong Yue; Qiaoyun Huang; Yu-Rong Liu (Geochimica et Cosmochimica Acta, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Molecular characterization of a novel chrysovirus isolated from the phytopathogenic fungus Fusarium commune - Wen Xin Huang; Li E Yang; Yan Bin Huang; Tao Sha Xu; Jie Zhong; Ya Rong Wang; Yan Song Xiao (Archives of Virology, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Corrigendum to “Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes” [J Hazard Mater 489 (2025) 137706] - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

The first set of Silurian marine red beds in South China: Spatiotemporal distribution, diachronism and paleogeographic significance - Xiaole Zhang; Jiayu Rong; Peng Tang; Renbin Zhan; Yi Wang; Zhongyang Chen; Ruiwen Zong; Bing Huang; Xin Wei (Science China Earth Sciences, 2025)

Dose-response pattern of marine macroalgae Gracilariopsis heteroclada to three fluoroquinolones and the cause-effect relationship of dose, growth, toxicity and sorption - Kun Lin; Youyou Guo; Rong Xin; Enyi Xie; Xuefeng Wang; Jianjun Cui; Jinhui Wu; Zhaowei Huang; Yong Liu; Shaoliang Lyu; Sipan Wang; Yongjian Huang; et al. (Algal Research, 2025)

Removal of antibiotic resistance from wastewater in aquatic ecosystems dominated by submerged macrophytes - Rong-min Zhang; Xiao-jie Chen; Ya-fei Li; Hui-zhen Tan; Wen-qing Huang; Ling-lin Li; Xin-ting Li; Jie Xie; Yun-xiao Chong; Xin-lei Lian; Xian-hui Huang (Journal of Hazardous Materials, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Parkinson's Disease and the Microbiota-Gut-Brain Axis: Metabolites, Mechanisms, and Innovative Therapeutic Strategies Targeting the Gut Microbiota - Zhao Ran; Ben-Rong Mu; Dong-Mei Wang; Xin-Huang; Quan-Hong Ma; Mei-Hong Lu (Molecular Neurobiology, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Cytochrome P450 CYP6EM1 confers resistance to thiamethoxam in the whitefly Bemisia tabaci (Hemiptera: Aleyrodidae) via detoxification metabolism - Mingjiao Huang; Peipan Gong; Cheng Yin; Jing Yang; Shaonan Liu; Buli Fu; Xuegao Wei; Jinjin Liang; Hu Xue; Chao He; Tianhua Du; Chao Wang; et al. (Pesticide Biochemistry and Physiology, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Nonradicals-dominated peroxymonosulfate activation of g-C3N4/CeO2 floating beads for enhanced inactivation of M. aeruginosa: Performance studies and mechanistic insights - Dandan Wang; Jing Li; Rong Zhang; Beiyu Xin; Xueru Huang; Yang Wang; Jifeng Guo (Chemical Engineering Journal, 2025)

Data-driven optimization reveals the impact of Urban Heat Island effect on the retrofit potential of building envelopes - Renge Li; Chenyu Huang; Weilin Xin; Jiahong Ye; Xue Zhang; Rong Qu; Jinyu Wang; Liang Yuan; Jiawei Yao (Building and Environment, 2025)

The Role of the Intestinal Flora and Its Derivatives in Neurocognitive Disorders: A Narrative Review from Surgical Perspective - Jian Huang; Tian-Shou Qin; Yun Bo; Yu-Jin Li; Rong-Sheng Liu; Yang Yu; Xiao-Dong Li; Jin-Can He; Ai-Xin Ma; Da-Peng Tao; Wen-Jun Ren; Jun Peng (Molecular Neurobiology, 2025)
Perioperative neurocognitive dysfunction is a significant concern for population health, impacting postoperative recovery and increasing the financial burden on patients. With an increasing number of surgical procedures being performed, the prevention and management of perioperative neurocognitive dysfunction have garnered significant attention. While factors such as age, lifestyle, genetics, and education are known to influence the development of cognitive dysfunction, recent research has highlighted the role of the gut microbiota in neurological health. An increased abundance of pro-inflammatory gut microbiota can trigger and worsen neuroinflammation, neuronal cell damage, and impaired cellular autophagy. Moreover, the inflammation-promoting gut microbiota can disrupt immune function, impair neuroautophagy, and affect the production and circulation of extracellular vesicles and neurotransmitters. These factors collectively play a role in the onset and advancement of cognitive impairment. This narrative review delves into the molecular mechanisms through which gut microbiota and their derivatives contribute to cognitive impairment, focusing on the impact of anesthesia surgery, changes in gut microbial populations, and perioperative cognitive impairment associations. The study suggests that alterations in the abundance of various bacterial species and their metabolites pre- and post-surgery may be linked to postoperative cognitive impairment. Furthermore, the potential of probiotics or prebiotics in addressing cognitive impairment is discussed, offering a promising avenue for investigating the treatment of perioperative neurocognitive disorders.

Nickel-iron layered double hydroxide and CoMoO4 composites supported on nickel foam as efficient bifunctional catalyst for water electrolysis - Xin Xiao; Rao Ma; Ke Jiang; Lushan Ma; Qiyao Wang; Shuang Meng; Tong Yang; Zhuo Qiu; Rong Hu; Long Huang (Fuel, 2025)

A novel measurement for evaluating the capture efficiency of local ventilation system using background oriented schlieren - Junhao Rong; Yanqiu Huang; Yihang Zhao; Yi Wang; Xin Li; Junwei Guo; Wenyang Wang; Shengnan Guo (Building and Environment, 2025)

Influence of Influent Load on Nitrification/Denitrification with MBBR for Oil Shale Retorting Wastewater Treatment: Performance and Microbial Community Structure - Rong-xin Zhang; Yi Liu; Dian-nan Huang; Li Zhang; Xing-guan Ma; Peng-fei Yu; Chuang Liu; Yong-yong Wang (Water, Air, & Soil Pollution, 2025)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Effects of different fermentation modes on tea leaves: Revealing the metabolites modification by quasi-targeted metabolomics - Xin Fang; Rong Xue; Jingyi Xiao; Qian Pu; Yufei Wang; Yuan Yuan; Bin Liu; Mengyuan Sui; Guangxian Jiang; Rida Niaz; Yongping Sun; Ziming Yu; et al. (Food Bioscience, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

Study on Translational toxicology of Senna obtusifolia aqueous extract - Xin Guo; Liping Gong; Chong Guo; Taotao Cai; Nana Huang; Xianhui Shen; Lisong Sheng; Rongrong Li; Yanqing Wang; Xinmei Zhao; Wenhe Guo; Rong Sun (Toxicon, 2024)

A novel chitosan/biochar-modified eco-concrete with balanced mechanical, planting, and water purification performance for riparian restoration - Fanrun Huang; Shengxiang Rong; Shiqiang Tao; Hongqiang Chu; Huajie Huang; Shuaixiao Gao; Xin Zhang; Xinyan Xiong; Chi Zhang (Journal of Cleaner Production, 2024)

Dynamic changes in the aroma profiles and volatiles of Enshi Yulu tea throughout its industrial processing - Guangxian Jiang; Rong Xue; Jun Xiang; Yufei Wang; Bin Liu; Yuan Yuan; Qian Pu; Xin Fang; Xingming Hu; Xiaoying Liu; Youyi Huang (Food Chemistry, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Simultaneous carbon, nitrogen and phosphorus removal in sequencing batch membrane aerated biofilm reactor with biofilm thickness control via air scouring aided by computational fluid dynamics - Chun-Hai Wei; Xin-Yu Zhai; Yu-Duo Jiang; Hong-Wei Rong; Li-Gong Zhao; Peng Liang; Xia Huang; Huu Hao Ngo (Bioresource Technology, 2024)

Effects of low-temperature stress on serum biochemical indicators, intestinal microbiome, and transcriptome of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Aquaculture International, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

Glutathione S-transferase directly metabolizes imidacloprid in the whitefly, Bemisia tabaci - Rong Zhang; Jing Yang; Jinyu Hu; Fengbo Yang; Jinjin Liang; Hu Xue; Xuegao Wei; Buli Fu; Mingjiao Huang; He Du; Chao Wang; Qi Su; et al. (Pesticide Biochemistry and Physiology, 2024)

Novel Pharmaceutical Cocrystals of Tegafur: Synthesis, Performance, and Theoretical Studies - Haoran Mei; Na Wang; Di Wu; Qi Rong; Xue Bai; Xin Huang; Lina Zhou; Ting Wang; Hongxun Hao (Pharmaceutical Research, 2024)

Chronic Pb exposure impairs learning and memory abilities by inhibiting excitatory projection neuro-circuit of the hippocampus in mice - Rong-Xin Zou; Xiaozhen Gu; Chenqing Huang; Hui-Li Wang; Xiang-tao Chen (Toxicology, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Application of hydrogen-assisted freezing technology: Promises and challenges - Lan Liao; Yao-Mian Chen; Jin-Peng Yang; Murtaza Ali; Xin-Xin Pang; Rong-Zeng Pan; Ze-Ling Huang; Xin-An Zeng (Trends in Food Science & Technology, 2023)

An independent framework-based evapotranspiration model (IFEM) for dual-source: From field to regional scale - Shuai Wang; Chaozi Wang; Chenglong Zhang; Weishu Wang; Pu Wang; Xin Zhang; Xingwang Wang; Yao Rong; Di Wang; Guanhua Huang; Zailin Huo (Remote Sensing of Environment, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Fabrication of depolymerized zein films via high-intensity ultrasound for ethylene adsorption packaging - Xin Fan; Ting Yang; Yuxin Li; Jinghua Zhao; Lingshuang Rong; Li Feng; Junrong Huang (Food Packaging and Shelf Life, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Soil core microbiota drive community resistance to mercury stress and maintain functional stability - Shuai Du; Xin-Qi Li; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Science of The Total Environment, 2023)

Lack of the CCT domain changes the ability of mango MiCOL14A to resist salt and drought stress in Arabidopsis - Shu-Quan Chen; Cong Luo; Yuan Liu; Rong-Zhen Liang; Xing Huang; Ting-Ting Lu; Yi-Hang Guo; Ruo-Yan Li; Chu-Ting Huang; Zhuo Wang; Xin-Hua He (Plant Science, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Method for quantitative extraction of copper hydroxide nanoparticles from farmland soil - Xin-Yuan Li; Yuan Yang; Peng Huang; Ying-Rong Wang; Yu-Lin Nie; Li Zhang; Qiang Wang (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Dry-to-wet fluctuation of moisture contents enhanced the mineralization of chloramphenicol antibiotic - Shuhan Huang; Qilin Wang; Zhenhui Fan; Min Xu; Rong Ji; Xin Jin; Cheng Gu (Water Research, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Four anti-inflammatory aromadendrane sesquiterpenoid fucosides and other constituents from Pittosporum glabratum var. neriifolium - Bai-Tong Sha; Rong Huang; Qiang-Guo Zhang; Sheng-Nan Guan; Jia-Qi Ding; Xin-Zheng Liu; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

Dynamic responses of root vigor, lipid peroxidation and antioxidant enzymes in Artemisia selengensis to long-term drought and re-watering - Hui-xiong Huang; Yun Cao; Kai-jing Xin; Rong-hua Liang; Yi-ting Chen; Jia-jun Qi (Aquatic Ecology, 2023)

Rice OsHsp16.9A interacts with OsHsp101 to confer thermotolerance - Yi-Hsin Liu; Tong-Seung Tseng; Ching-Rong Wu; Shu-Ting Cho; Chih-Horng Kuo; Xin-Jie Huang; Jung-Yi Cheng; Kuo-Hsuan Hsu; Kung-Fu Lin; Chia-Chin Liu; Ching-Hui Yeh (Plant Science, 2023)

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

Controllable acoustic deterrent based on the warning signals generated by nonel detonators - Long-Fei Huang; Xiao-Mei Xu; Yi Tao; Rong-Xin Wang; Yang-Liang Zhou; Fang-Gui Xiao (Marine Pollution Bulletin, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Spinal cord astrocyte P2X7Rs mediate the inhibitory effect of electroacupuncture on visceral hypersensitivity of rat with irritable bowel syndrome - Zhi-jun Weng; Shi-xiu Hu; Fang Zhang; Zhi-ying Zhang; Yun Zhou; Min Zhao; Yan Huang; Yu-hu Xin; Huan-gan Wu; Hui-rong Liu (Purinergic Signalling, 2023)

Effects of low-temperature stress on intestinal structure, enzyme activities and metabolomic analysis of juvenile golden pompano (Trachinotus ovatus) - Rong-xin Li; Eric Amenyogbe; Yi Lu; Jing-hui Jin; Rui-tao Xie; Jian-sheng Huang (Frontiers in Marine Science, 2023)
Water temperature plays a crucial role in the growth, survival, and reproduction of fish species, as they make up the majority of aquatic fauna. In this study, the effects of low temperature were studied on the functional state of juvenile golden pompano ( Trachinotus ovatus ) under low-temperature stress. The study was conducted at 28°C in the control group and 18°C in the cold group for 14 d to determine the intestinal tissue, digestive and antioxidant enzyme activities, and metabolites of juvenile fish. The results showed that: (1) the swelling degree of the muscle layer deepened and was congested with a longer low-temperature stress period. The folds were sparse, from slight swelling to shedding and deformation. The intestinal mucosa was necrotic and had vacuoles, and the number gradually increased. Serious erosion of the villi occurred. (2) The specific activities of digestive enzymes showed a downward trend. (3) The intestinal superoxide dismutase (SOD) activity, malondialdehyde (MDA) content, and glutathione peroxidase (GSH-Px) activity showed an upward trend. The intestinal catalase (CAT) activity showed a downward trend. (4) Compared with the control group, there were 28 metabolites in the cold group showing significant differences, among which Z, 11Z, 14Z-eicosatrienoic acid, stearic acid, and adrenic acid showed an upward trend. In contrast, spermidine and uracil showed a downward trend. Among the enriched metabolic pathways, the main differential pathways were unsaturated fatty acid biosynthesis, fatty acid biosynthesis, linoleic acid metabolism, pyrimidine metabolism, and β-alanine metabolism. According to metabolomic analysis, under low-temperature stress, the fish body improved the synthesis of unsaturated fatty acids and saturated fatty acids to adapt to a low-temperature environment and consumed spermidine to improve its immune ability to clear the peroxide generated by the synthesis of unsaturated fatty acids in the body so that the cells were protected from oxidative damage. After 14 days, low-temperature stress affected metabolites and enzyme activity indices in juvenile golden pompano. Low-temperature stress causes changes in intestinal antioxidants and digestive enzymes and damage intestinal tissues. As a result of this exploration of how low temperatures affect the juvenile golden pompano, the foundation is laid for future studies, such as the molecular mechanisms of low-temperature adaptation in fish species.

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

An integrated process for co-producing fermentable sugars and xylonate from sugarcane bagasse based on xylonic acid assisted pretreatment - Zhen Zhu; Rong Huang; Shuangquan Yao; Yiruo Liu; Qibo Zhang; Xin Zhou; Kankan Jiang (Bioresource Technology, 2023)

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Genetic Diversity Analysis of Sugarcane (Saccharum spp. hybrids) Among High-Sucrose Clones of GT Series and Commonly Used Parents by Using Microsatellite Markers in Guangxi, China - Hai-Rong Huang; Yi-Jing Gao; Mukesh Kumar Malviya; Krishan K. Verma; Manoj Kumar Solanki; Yu-Xin Huang; Xiang Li; Yuchi Deng; Jing Yan; Shi-Yun Tang; Lun-Wang Wang; Lin Xu (Sugar Tech, 2022)

Caffeine Inhibits Activation of the NLRP3 Inflammasome via Autophagy to Attenuate Microglia-Mediated Neuroinflammation in Experimental Autoimmune Encephalomyelitis - Hui-Qi Wang; Kai-Yi Song; Jin-Zhou Feng; Si-Yuan Huang; Xiu-Ming Guo; Lei Zhang; Gang Zhang; Ying-Chao Huo; Rong-Rong Zhang; Yue Ma; Qing-Zhe Hu; Xin-Yue Qin (Journal of Molecular Neuroscience, 2022)

Genomic molecular signatures determined characterization of Mycolicibacterium gossypii sp. nov., a fast-growing mycobacterial species isolated from cotton field soil - Rui-Rui Huang; Shen-Rong Yang; Cheng Zhen; Xian-Feng Ge; Xin-Kai Chen; Zhi-Qiang Wen; Ya-Nan Li; Wen-Zheng Liu (Antonie van Leeuwenhoek, 2021)

Seasonal variation of flavonoid metabolites in leaves of Liquidambar formosana ‘Nanlinhong’ trees revealed by UPLC-ESI–MS/MS - Jiu-Xin Lai; Fu-Rong Lin; Ping Huang; Wen-Ying Guo; Lie-Bao Han; Yong-Qi Zheng (Brazilian Journal of Botany, 2021)

Comparative Transcriptomic Analyses of Haemophilus parasuis Reveal Differently Expressed Genes among Strains with Different Virulence Degrees - Yuan Y. Zhou; Chao Wang; Jing Yuan; Rong L. Yin; Xin Chen; Rui Li; Xue L. Zhang; Jing Wang; Chen Huang; Rong H. Yin (Current Microbiology, 2021)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Development and characterization of novel microsatellite markers in chestnut tiger butterfly Parantica sita (Lepidoptera: Nymphalidae) using next-generation sequencing - Ping Hu; Chia-Lung Huang; Min-Xin Luo; Yu-Feng Hsu; Rong-Jiang Wang (Applied Entomology and Zoology, 2020)

Excess copper effects on growth, uptake of water and nutrients, carbohydrates, and PSII photochemistry revealed by OJIP transients in Citrus seedlings - Qiang Li; Huan-Huan Chen; Yi-Ping Qi; Xin Ye; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Environmental Science and Pollution Research, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

Selective and novel cyclin-dependent kinases 4 inhibitor: synthesis and biological evaluation - Qingxiang Guo; Yongtao Li; Chao Zhang; Zhi Huang; Xin Wang; Yongwei Nie; Yao Li; Yanhua Liu; Shengyong Yang; Rong Xiang; Yan Fan (Medicinal Chemistry Research, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

A new flavonoid from Sophora flavescens Ait. - Rong Huang; Yi Liu; Lin-Lin Zhao; Xi-xin Chen; Feng Wang; Wei Cai; Lei Chen (Natural Product Research, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Exploration of cultivable fungal communities in deep coal‐bearing sediments from ∼1.3 to 2.5 km below the ocean floor - Chang‐Hong Liu; Xin Huang; Tian‐Ning Xie; Ning Duan; Ya‐Rong Xue; Tan‐Xi Zhao; Mark A. Lever; Kai‐Uwe Hinrichs; Fumio Inagaki (Environmental Microbiology, 2017)
Summary Although subseafloor sediments are known to harbour a vast number of microbial cells, the distribution, diversity, and origins of fungal populations remain largely unexplored. In this study, we cultivated fungi from 34 of 47 deep coal‐associated sediment samples collected at depths ranging from 1289 to 2457 m below the seafloor (mbsf) off the Shimokita Peninsula, Japan (1118 m water depth). We obtained a total of 69 fungal isolates under strict contamination controls, representing 61 Ascomycota (14 genera, 23 species) and 8 Basidiomycota (4 genera, 4 species). Penicillium and Aspergillus relatives were the most dominant genera within the Ascomycetes, followed by the members of genera Cladosporium , Hamigera , Chaetomium , Eutypella , Acremonium , Aureobasidium , Candida , Eurotium , Exophiala , Nigrospora , Bionectria and Pseudocercosporella . Four Basidiomycota species were identified as genera Schizophyllum , Irpex , Bjerkandera and Termitomyces . Among these isolates, Cladosporium sphaerospermum and Aspergillus sydowii relatives were isolated from a thin lignite coal‐sandstone formation at 2457 mbsf. Our results indicate that these cultivable fungal populations are indigenous, originating from past terrigenous environments, which have persisted, possibly as spores, through ∼20 million years of depositional history.

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Genome-wide analysis of Gro/Tup1 family corepressors and their responses to hormones and abiotic stresses in maize - Hongyou Li; Kaifeng Huang; Hanmei Du; Hongling Wang; Xin Chen; Shibin Gao; Hailan Liu; Moju Cao; Yanli Lu; Tingzhao Rong; Suzhi Zhang (Journal of Plant Biology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Textural and map contrasts of the subduction-collision boundary between the Philippine Arc and the Sunda margin - Zhou-rong Cai; Jun-yang Xiang; Qiang-tai Huang; Zheng-xin Yin; Yong-jian Yao; Hai-ling Liu; Bin Xia (Arabian Journal of Geosciences, 2016)

Preparation of Bacterial Cellulose/Inorganic Gel of Bentonite Composite by In Situ Modification - Bo Wang; Gao-xiang Qi; Chao Huang; Xiao-Yan Yang; Hai-Rong Zhang; Jun Luo; Xue-Fang Chen; Lian Xiong; Xin-De Chen (Indian Journal of Microbiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Rhodococcus agglutinans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Ling Meng; Yan-Yan Duan; Rui Gao; Jian-Xin Zhang; Jian-Rong Huang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Abundance and distribution of fatty acids in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Journal of Ocean University of China, 2015)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

The rescuable function and mechanism of resveratrol on As2O3-induced hERG K+ channel deficiency - Xin Zhao; Kai-ping Zhang; Ting Huang; Cai-Chuan Yan; Li-Rong Liu; Qi-Lei Zhu; Feng-Feng Guo; Chen Liu; Bao-Xin Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Component characteristics of polycyclic aromatic compounds in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Acta Oceanologica Sinica, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Cloning and expression analysis of a novel high-mobility group box 2 homologue from Lampetra japonica - Pang Yue; Xiao Rong; Xue Zhuang; Huang Jin Sha; Jin Min Li; Liu Xin; Qing Wei Li (Fish Physiology and Biochemistry, 2014)

Component characteristics of organic matter in hydrothermal barnacle shells from Southwest Indian Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Huijing Zhao; Baoju Yang; Kunbo Rong; Yao Ma (Acta Oceanologica Sinica, 2013)

Effect of sand-stabilizing shrubs on soil respiration in a temperate desert - Zhi-Shan Zhang; Xin-Rong Li; Robert S. Nowak; Pan Wu; Yan-Hong Gao; Yang Zhao; Lei Huang; Yi-Gang Hu; Rong-Liang Jia (Plant and Soil, 2013)

Soil oxidases recovered faster than hydrolases in a 50-year chronosequence of desert revegetation - Zhi-Shan Zhang; Xue-Jun Dong; Yu-Bin Liu; Xin-Rong Li; Rong-Liang Jia; Yi-Gang Hu; Ming-Zhu He; Lei Huang (Plant and Soil, 2012)

Proteomic analysis of the nuclear phosphorylated proteins in dairy cow mammary epithelial cells treated with estrogen - Jian-guo Huang; Xue-jun Gao; Qing-zhang Li; Li-min Lu; Rong Liu; Chao-chao Luo; Jia-li Wang; Qiao Bin; Xin Jin (In Vitro Cellular & Developmental Biology - Animal, 2012)

Curcumin inhibits proliferation of human lens epithelial cells: a proteomic analysis - Yan-hong Hu; Xiu-rong Huang; Ming-xin Qi; Bu-yuan Hou (Journal of Zhejiang University-SCIENCE B, 2012)

The expression of a new HD-Zip II gene, MSHB1, involving the inhibitory effect of thidiazuron on somatic embryogenic competence in alfalfa (Medicago sativa L. cv. Jinnan) callus - Xin Hu; Chun-Rong Zhang; Hui Xie; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Acta Physiologiae Plantarum, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)

Inhibition of Endogenous Hydrogen Sulfide Generation is Associated with Homocysteine-Induced Neurotoxicity: Role of ERK1/2 Activation - Xiao-Qing Tang; Xin-Tian Shen; Yi-E Huang; Rong-Qian Chen; Yan-Kai Ren; Heng-Rong Fang; Yuan-Yuan Zhuang; Chun-Yan Wang (Journal of Molecular Neuroscience, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

A New “Switch-On” Fluorescence Chemosensor for Anions via Modulation of Intraligand and Metal-to-Ligand Charge-Transfer Emission in a Pd(II)-based Receptor - Li-Rong Lin; Qin-Juan Xu; Xin Wu; Rong-Bin Huang; LanSun Zheng (Journal of Fluorescence, 2011)

2ME and 2OHE2 exhibit growth inhibitory effects and cell cycle arrest at G2/M in RL95-2 human endometrial cancer cells through activation of p53 and Chk1 - Qian-fen Gong; E-hu Liu; Rong Xin; Xiuning Huang; Ning Gao (Molecular and Cellular Biochemistry, 2011)

Genetic Diversity and Geographical Differentiation of Desmodium triflorum (L.) DC. in South China Revealed by AFLP Markers - Mao-feng Yue; Ren-chao Zhou; Ye-lin Huang; Guo-rong Xin; Su-hua Shi; Li Feng (Journal of Plant Biology, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Medium optimization for the feather-degradation by Streptomyces fradiae Var S-221 using the response surface methodology - Xin Cheng; Lin Huang; Xiao-rong Tu; Kun-tai Li (Biodegradation, 2010)

Changes of Porcine Growth Hormone and Pituitary Nitrogen Monoxide Production as a Response to Cadmium Toxicity - Xin-Yan Han; Qi-Chun Huang; Bo-Jing Liu; Zi-Rong Xu; Yi-Zhen Wang (Biological Trace Element Research, 2007)

Isolation and characterization of a human putative receptor protein kinase cDNA STYK1* - Xin Ye; Chaoneng Ji; Qingshan Huang; Chao Cheng; Rong Tang; Jian Xu; Li Zeng; Jianfeng Dai; Qihan Wu; Shaohua Gu; Yi Xie; Yumin Mao (Molecular Biology Reports, 2003)